The Effect of Ice Breaking on Learning Motivation for Children aged 5-6 Years at RA Ilyasa Nurul Qomar in 2022 - Nurkholis, Islamiyah; Purwani, Annisa; Anugrah, Yuwan Fijar (International Conference on Islamic Studies, 2022)
Teachers as educators must try to create motivation in children by growing and developing children's interest in learning a field of study to be taught. Based on observations made by researchers in early childhood in the 5-6 year age group, students of RA Ilyasa Nurul Qomar often experience problems in their learning. Most students find it difficult to pay attention to the teacher during learning, and students of RA Ilyasa Nurul Qomar tend to prefer active learning that can move all the five sensory functions of students. Author will conduct research related to increasing students learning motivation through ice breaking. This ice breaking activities carried out by this ice breaking are varied, so that students will feel happy while learning. Based on the calculation of the paired sample t test and the independent sample test, the value of sig (2 tailed) = 0.00 ≤ 0.05, then H0 is rejected and H1 is accepted. Based on the calculations and the basis for making decisions from the two hypothesis tests, it was concluded that there was a significant effect of ice breaking on the learning motivation of children aged 5-6 years at RA Ilyasa Nurul Qomar.